2010
DOI: 10.1111/j.1540-4781.2010.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

The Professional Development of Future Professors of Foreign Languages: Looking Back, Looking Forward

Abstract: Although the professional development of graduate students in foreign language (FL) departments is of critical importance, discussion of its significance and evolution was all but absent in the 2007 Modern Language Association report “Foreign Languages and Higher Education: New Structures for a Changed World,” a document advocating curricular and structural reforms of FL departments in forthright terms. This lacuna drove the current review, which traces the forms and foci of research appearing from 1987 to 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 60 publications
0
27
0
1
Order By: Relevance
“…At the same time, LTI research needs to be interpreted in relation to the ways second and foreign language teacher education research has evolved over time. While Schulz (), for example, focused on skills in her historical review of foreign language teacher development between 1916–1999, a decade later, the review of Allen and Negueruela–Azarola () identified the importance of beliefs and identities with respect to FL teaching experiences, investigated in the context of increasingly sophisticated theoretical frameworks and research designs. In short, LTI research has witnessed much theoretical and methodological innovation in the last two decades, and it is to these two broad paths of innovation that we turn next.…”
Section: Identity Research On Language Learning and Teachingmentioning
confidence: 99%
“…At the same time, LTI research needs to be interpreted in relation to the ways second and foreign language teacher education research has evolved over time. While Schulz (), for example, focused on skills in her historical review of foreign language teacher development between 1916–1999, a decade later, the review of Allen and Negueruela–Azarola () identified the importance of beliefs and identities with respect to FL teaching experiences, investigated in the context of increasingly sophisticated theoretical frameworks and research designs. In short, LTI research has witnessed much theoretical and methodological innovation in the last two decades, and it is to these two broad paths of innovation that we turn next.…”
Section: Identity Research On Language Learning and Teachingmentioning
confidence: 99%
“…In fact, this research could contribute to "developing empirical models of second-language writing instruction that do justice to the full nature of this phenomenon" [78] (Cumming, 2001, p. 209). Moreover, it provided an opportunity "to share insights, experiences, and tools across universities, particularly as many are solely responsible for teachers' professional development in their department" [79] (Allen & Negueruela-Azarola, 2010, p. 389). In addition, focusing on students' written errors raises the awareness of teachers to be more humanistic in their treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Siskin's research, as well as the bilingual teacher studies, point to the connections between teacher identities and pedagogies (Varghese et al, ). While Allen and Negueruela–Azarola () argue that FL teaching assistants should learn to reflect on how their identities influence their approach to teaching, little research has been conducted on the intercultural identities of FL teachers.…”
Section: Review Of Literaturementioning
confidence: 99%